Ranganathan : Apostle of Librarianship - Rangra, V.K. (DESIDOC Journal of Library & Information Technology, 2002)
Focuses attention on the human aspects of the personality of Dr SR Ranganathan. Describes his entry into the profession and the problems he faced. Gives briefly his contributions and achievements. Traces his leanings towards spiritualism and mysticism and their influence on his work. Gives instances of his interest in literature, poetry and music. Comments on his style in writing and public speaking. Pleads that to pay a befitting homage to him, more so in his Centenary Year, Ranganathan should be posthumously honoured with the highest possible Republic-Day Award. http://dx.doi.org/10.14429/dbit.12.5.3067